2013
DOI: 10.1093/jmicro/dfs086
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscope structural study of the zona radiata in the oocyte of zebrafish (Danio rerio)

Abstract: Teleosts account for more than half of the vertebrate species. A key feature of the evolutionary success of teleosts is their reproductive systems, which are efficient and functional under all aquatic environmental conditions. The zona radiata (ZR) is a non- cellular envelope over oolemma of teleost fish oocytes. The morphology of the ZR varies in different ovarian developmental stages and also among various fish species, which reflects adaptation to ecological conditions. In this research the structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Studies on fish reproduction assist the conservation of germplasm resources and the investigation of animal reproductive regulation mechanism in fish model. Most studies on fish oogenesis focus on the structural changes during oocyte maturation observed by light and electron micrograph sections and the regulation of endocrine factors ( Selman et al, 1993 ; Tyler and Sumpter, 1996 ; Patiño et al, 2005 ; Kaviani et al, 2013 ). Conventional genome analysis approaches have been used to capture global gene expression patterns and chromatin conformation of fish ovaries or oocytes ( Shao et al, 2014 ; Can et al, 2020 ; Dong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on fish reproduction assist the conservation of germplasm resources and the investigation of animal reproductive regulation mechanism in fish model. Most studies on fish oogenesis focus on the structural changes during oocyte maturation observed by light and electron micrograph sections and the regulation of endocrine factors ( Selman et al, 1993 ; Tyler and Sumpter, 1996 ; Patiño et al, 2005 ; Kaviani et al, 2013 ). Conventional genome analysis approaches have been used to capture global gene expression patterns and chromatin conformation of fish ovaries or oocytes ( Shao et al, 2014 ; Can et al, 2020 ; Dong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the oocytes collected from our Astyanax mexicanus populations were between the vitellogenesis and maturation phase (555.9-822.4 μm). Kaviani et al (2013) described a similar classification for oocyte maturation stages in zebrafish (Danio rerio), so when comparing those with our Astyanax mexicanus, our oocytes were at the maturation stage. In zebrafish the diameter of the oocytes in this phase was 412.75 μm and the thickness of the chorion was 1.6 μm, very similar to values observed for our Astyanax mexicanus oocytes (555.9-822.4 μm, 1.1-1.5 μm respectively).…”
Section: Maturation Stages Of Astyanax Mexicanus Gametesmentioning
confidence: 62%
“…The kidneys were taken after dissection and fixed in formaldehyde 10%, dehydrated by alcohol, impregnated, paraffin embedded, and 3 µm sections were prepared. The haematoxylin and eosin H & E and periodic acid-schiff (PAS) staining were performed for light microscopy ( 14 ). For electron microscopy, after fixation in glutaraldehyde 2.5% and dehydration in acetone, the samples were embedded in araldite resin medium (Proscitech, Australia) and 50 nm sections were prepared and stained with uranyl acetate and lead nitrate ( 15 ).…”
Section: Methodsmentioning
confidence: 99%